IN VITRO FREE RADICAL SCAVENGING ACTIVITY OF BAUHINIA RACEMOSA - Bhaskar, Bhagya; Avadhani, Ramakrishna (Journal of Health and Allied Sciences NU, 2012)
In vitro free radical scavenging activity of aqueous and ethanolic bark extracts of Bauhinia racemosa was assessed by studying its ability to scavenge DPPH, Nitric oxide, hydroxyl radical and reducing power. Both the extracts showed effective free radical scavenging activity. Ethanolic extract was comparatively more potential than aqueous extract. The results support its traditional use in various ailments and as a source of natural antioxidants which protect cells against oxidative stress.
Keywords: Bauhinia racemosa; Phytochemicals; DPPH; Nitric oxide; hydroxyl radical; reducing power